Incentives and Effort in the Public Sector : Have U.S. Education Reforms Increased Teachers? Work Hours? - Christiana Stoddard; Peter Kuhn (Institute for the Study of Labor (IZA), 2004)
Beyond some contracted minimum, salaried workers? hours are largely chosen at the worker?s discretion and should respond to the strength of contract incentives. Accordingly, we consider the response of teacher hours to accountability and school choice laws introduced in U.S. public schools over the past two decades. Total weekly hours of full-time teachers have risen steadily since 1983 by about an hour, and after-school instructional hours have increased 34 percent since 1987. Average hours and the rate of increase also vary widely across states. However, after accounting for a common time trend in hours, we find no association between the introduction of accountability legislation and the change in teacher hours. We conjecture that the weak link between effort and compensation in most school reforms helps explain the lack of such an association.
Keywords: J45; J44; J22; I28; I21; 330; teachers; labor supply; work hours; education reform; Lehrkräfte; Arbeitsangebot; Arbeitszeit; Bildungsreform; Ökonomischer Anreiz; Schätzung; Vereinigte Staaten